2010
DOI: 10.1002/ibd.21179
|View full text |Cite
|
Sign up to set email alerts
|

Serum anti-glycan antibodies predict complicated Crohnʼs disease behavior

Abstract: This is the first study showing the clinical value of serum antiglycan antibodies for prediction of a more complicated disease course in adult patients with CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 24 publications
2
72
1
4
Order By: Relevance
“…Seow et al have shown that an increasing number of positive antibodies is associated with early CD onset, fistulating and perianal disease, and increased risk for surgery [12]. These findings were confirmed by Rieder et al who showed that a higher number of anti-glycan antibodies predicts a faster progression toward more severe disease [18]. Anti-GM-CSF antibody also correlates with disease activity and an increased risk of relapses [10].…”
Section: Prediction Of Disease Stratification and Severity In CDmentioning
confidence: 85%
“…Seow et al have shown that an increasing number of positive antibodies is associated with early CD onset, fistulating and perianal disease, and increased risk for surgery [12]. These findings were confirmed by Rieder et al who showed that a higher number of anti-glycan antibodies predicts a faster progression toward more severe disease [18]. Anti-GM-CSF antibody also correlates with disease activity and an increased risk of relapses [10].…”
Section: Prediction Of Disease Stratification and Severity In CDmentioning
confidence: 85%
“…[37][38][39][40] These biomarkers predict and are qualitatively and quantitatively associated with an aggressive and complicated course of Crohn's disease, including stricturing and/or penetrating phenotype, both in adult and paediatric patients. 13 However, a recent study showed that none of the anti-glycan antibodies ASCA, AMCA, ACCA, ALCA, anti-L and anti-C correlates with disease phenotype.…”
Section: Antimicrobial Antibodiesmentioning
confidence: 99%
“…Antibodies specific to N-glycolylneuraminic acid, a glycan generated by non-human cell lines, are reported to comprise up to 0.1-0.2% of circulating IgG in normal humans (37). Antibodies specific to other glycans have been associated with adult and pediatric Crohn's disease progression (38)(39)(40)(41) (Table I).…”
Section: Nature and Characterization Of Pre-existing Reactivity In Admentioning
confidence: 99%
“…Associated with Crohn's disease (39,40) Gal-β-1-3-GalNAc-α GalNAc-α Tumor-associated antigens (41) Several pegylated biologics that have received regulatory approval include PegIntron ™ (pegylated interferon-alpha 2b), Pegasys ™ (pegylated interferon-alpha 2) Neulasta ™ (pegylated granulocyte colony stimulating factor), Mircera ™ (methoxy polyethylene glycol-epoetin beta), and Oncaspar ™ (pegylated L-asparaginase derived from E. coli).…”
Section: Pegylated Biologic Proteinsmentioning
confidence: 99%